2009
DOI: 10.17796/jcpd.34.1.l1773mh5pw2745g6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators for Signs and Symptoms of Temporomandibular Dysfunction in Children

Abstract: Objectives: The aim of this study was to determine the risk indicators for signs and symptoms of temporomandibular dysfunction (TMD) in children between 4 and 12 years of age. Study Design: One hundred six patients were assessed for the following variables:(1) signs and symptoms of TMD (deviation when opening mouth, joint noises, limitation of movement, pain in the mandible or during movement), (2) dentition and occlusal abnormalities, and 3) habits (pacifier sucking, nonnutritive sucking, finger sucking, nail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 24 publications
1
49
0
5
Order By: Relevance
“…1 Previous studies have shown a multifactorial etiology of TMD, with malocclusion being a potential risk factor. 2 Previous reports have also indicated that malposition of the mandibular condyle relative to the glenoid fossa may be one of the important causes of TMD [3][4][5][6] and that orthodontic treatment and an anterior repositioning splint are effective in treating TMD with a retropositioned condyle. 7 Skeletal class II malocclusion cases with a steep mandible are difficult to treat because of their vertical growth pattern.…”
mentioning
confidence: 99%
“…1 Previous studies have shown a multifactorial etiology of TMD, with malocclusion being a potential risk factor. 2 Previous reports have also indicated that malposition of the mandibular condyle relative to the glenoid fossa may be one of the important causes of TMD [3][4][5][6] and that orthodontic treatment and an anterior repositioning splint are effective in treating TMD with a retropositioned condyle. 7 Skeletal class II malocclusion cases with a steep mandible are difficult to treat because of their vertical growth pattern.…”
mentioning
confidence: 99%
“…The method for diagnosis of TMD was also quite varied: 20% of the articles used the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) with different approaches, 20% used clinical examination of signs and symptoms based on Bonjardim et al, and the others used questionnaires and/or examinations prepared by the authors …”
Section: Resultsmentioning
confidence: 99%
“…Eight of the selected studies had a positive and statistically significant association between bruxism in children and TMD, according to the variables they analyzed ( P < 0.05) …”
Section: Resultsmentioning
confidence: 99%
“…In a population of children, Pereira et al (2009) did not find any correlation between malocclusion and TMD but they identified bruxism and posterior cross bite as risk factors for TMD. Tecco et al (2010a) and Tecco & Festa (2011) found a correlation between TMD with painful symptoms in children (5-15 years of age) and unilateral cross bite, but not with TMJ sounds.…”
Section: Occlusion and Tmdmentioning
confidence: 85%
“…Le Resche et al (2005) pointed to the higher prevalence of pain, including TMD pain (in terms of multiple pain problems) during pubescent development of girls. Pereira et al (2009) found at least one sign or symptom of TMD in 12.26% of children aged between 4-12 (in 5 boys and 8 girls). Bonjardim et al (2003) determined a low prevalence of TMD signs and symptoms in children aged between 3 and 5 (primary dentition): 3.03% had TMJ sounds and 4.04% had jaw pain without any gender differences.…”
Section: Epidemiology Of Tmd and The Use Of Mrimentioning
confidence: 91%